Psychological distress is more prevalent in fertile age and premenopausal women with PCOS symptoms: 15-year follow-up - Karjula, S; Morin-Papunen, L; Auvinen, J; Ruokonen, A; Puukka, K; Franks, S; Jarvelin, M-R; Tapanainen, JS; Jokelainen, J; Miettunen, J; Piltonen, TT (The Journal of Clinical Endocrinology & Metabolism, 2017)
Context: Polycystic ovary syndrome (PCOS) is associated with increased psychological distress, obesity and hyperandrogenism being suggested as key promoters. Objectives: To investigate the prevalence of anxiety/depression and their coexistence in women with PCOS/PCOS-related symptoms at ages 31 and 46. The roles of obesity, hyperandrogenism, and awareness of PCOS on psychological distress were also assessed. Design: Population-based follow-up. Setting: Northern Finland Birth Cohort 1966 with 15-year follow-up. Participants: At age 31, a questionnaire-based screening for oligoamenorrhea (OA) and hirsutism (H): 2188 asymptomatic (controls), 331 OA, 323 H, and 125 OA plus H (PCOS). Follow-up at age 46: 1576 controls, 239 OA, 231 H, and 85 PCOS. Interventions: Questionnaire-based screening for anxiety and depression symptoms (Hopkins Symptom Checklist-25) and previously diagnosed/treated depression at ages 31 and 46. Body mass index (BMI), serum testosterone/free androgen index, and awareness of polycystic ovaries/PCOS on psychological distress were also assessed. Main Outcomes: Population-based prevalence of anxiety and/or depression in women with PCOS/PCOS-related symptoms at ages 31 and 46. Results: Anxiety and/or depression symptoms, their coexistence, and rate of depression were increased at ages 31 and 46 in women with PCOS or isolated H compared with controls. High BMI or hyperandrogenism did not associate with increased anxiety or depression symptoms. The awareness of PCOS was associated with increased anxiety. Conclusions: Women with PCOS or isolated H present more often with anxiety and/or depression symptoms and their coexistence compared with controls. High BMI or hyperandrogenism did not provoke psychological distress in PCOS. The awareness of PCOS increased anxiety but did not associate with severe anxiety or depression.